METHODS OF MULTICRITERION EVALUATION OF REGIONAL ECONOMIC SECURITY OF RUSSIA (CASE OF THE VOLGA FEDERAL DISTRICT) - Dmitriy N. Lapaev; Evgeniy S. Mityakov (Статистика и экономика, 2016)
The article suggests methods for multicriterion evaluation of regional economic security of Russia. Unequal development conditions of Russian regions create additional dangers and challenges for economic security of the country. Accordingly, a quite actual task is to ensure monitoring and comparative evaluation of economic security of the Russian Federation regions. Conducting a multicriterion evaluation for all regions is a complicated and unobvious procedure. Therefore the authors test the methods on the example of the Volga Federal District. As the result ranks of solution of the multicriterion evaluation tasks are determined.